2019
DOI: 10.1002/app.47763
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of dispersible nanosilica surface‐capped by hexamethyl disilazane via anin situsurface‐modification method and investigation of its effects on the mechanical properties of styrene–butadiene/butadiene rubber

Abstract: Silica has been established as one of the most promising materials in green tires. The filler–rubber interactions can increase the comprehensive performance of rubber composites. In this study, sodium silicate was used as the silicon source and hexamethyl disilazane (HMDS; molecular formula: C6H19NSi2) was used as a modifier to synthesize dispersible silica (DNS) via an in situ surface‐modification method. The effects of the HMDS‐capped silica on the properties of rubber–matrix composites made of styrene–butad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the process of tire preparation, the amount of filler accounts for more than 1/3 of the amount of tire rubber formula, and is becoming one of the most important materials in the tire rubber composition [ 7 , 8 ]. Compared with the high economic cost and serious environmental pollution caused by traditional fillers (carbon black), the “green tire” has become the main direction of automotive tire design and development [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of tire preparation, the amount of filler accounts for more than 1/3 of the amount of tire rubber formula, and is becoming one of the most important materials in the tire rubber composition [ 7 , 8 ]. Compared with the high economic cost and serious environmental pollution caused by traditional fillers (carbon black), the “green tire” has become the main direction of automotive tire design and development [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…9,14 Silane coupling agents such as bis(3-triethoxysilylpropyl) tetrasulfide (Si69) and hexamethyldisilazane (HMDS), can be incorporated into the surface of silica, thereby significantly increasing the dispersion and improving the mechanical properties of rubber matrix composites. [15][16][17][18][19][20][21][22] Under optimal mixing conditions, using Si69 significantly minimizes the agglomerate formation and enhances the rubber-filler compatibility. 23 However, in rubber-filler dispersion, the quantity of coupling agent utilized is a crucial factor; increasing the amount of coupling agent may result in complicated viscoelastic properties of the rubber.…”
Section: Introductionmentioning
confidence: 99%
“…A widely used method for modifying the surface of SiO 2 particles is to chemically bond a silane agent through a reaction involving the alkoxy groups of the silane and the hydroxyl groups present on the SiO 2 surface 9,14 . Silane coupling agents such as bis(3‐triethoxysilylpropyl) tetrasulfide (Si69) and hexamethyldisilazane (HMDS), can be incorporated into the surface of silica, thereby significantly increasing the dispersion and improving the mechanical properties of rubber matrix composites 15–22 . Under optimal mixing conditions, using Si69 significantly minimizes the agglomerate formation and enhances the rubber‐filler compatibility 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies had shown that it was because the surface of silica was covered by surfactant, which reduced the exposure of the silanols. 22,23 In summary, the reduction of silanol on the surface of silica can improve its compatibility with rubber matrix.…”
Section: Introductionmentioning
confidence: 99%